Primary criteria of buying shoe decision among female students using fuzzy analytical hierarchy process / Mazidatul Liana Meor Hussin - Meor Hussin, Mazidatul Liana (2021)
Fuzzy Analytical Hierarchy Process (F-AHP) is one of the popular methods to study non-numerical data. Non-numerical data refers to the criteria for buying shoe decisions among female students. Various criteria influence a student to buy their shoes. Thus, this study aims to formulate a model that can evaluate the most highlighted criteria of the buying shoe decision. This research involves four main criteria whenever a decision to buy shoes is made. Those criteria are fashion, material, durability, and price. The data in this study were collected by the researcher through distributing questionnaires to several shoe shops in Arau and Kangar as they are the nearest shop the students can go. Next, the solutions were analyzed by using Microsoft (MS) Excel. From the results obtained, the criterion with the highest weight is price with 0.4742, followed by durability with 0.2763, material with 0.1279, and lastly, fashion with 0.1216. From the value above, it was analyzed that price influence students the most when buying shoes. This model can also be used with other non-numerical data to evaluate the criteria of preference.